IMPLEMENTATION OF THE ELECTRONIC TRANSACTION LAW (UU ITE) REVIEWED BASED ON THE BOOK OF CRIMINAL LAW (KUHP) ON FREEDOM OF COMMUNITY EXPRESSION IN SOCIAL MEDIA - Zariah Nur; Mahzaniar Mahzaniar (SEAN Institute, 2022)
This study aims to determine the implementation of the Electronic Transaction Law (Uu Ite) in terms of the Criminal Code (KUHP) on the Freedom of Expression of the Community on Social Media. Social media is an online medium, with its users being able to easily participate, share, and create content including blogs, social networks, wikis, forums and virtual worlds. Blogs, social networks and wikis are the most common forms of social media used by people around the world. Deliberately and without rights distributing and/or transmitting and/or making accessible Electronic Information and/or Electronic Documents containing insults and/or defamation with decision number 61/Pid.B/2020/PN Mdn. The government has played a role in law enforcement in the field of Information and Electronic Transactions (ITE) with the enactment of Law No. 11 of 2008 concerning ITE. The Government of the Republic of Indonesia through law enforcement officials, especially the National Police, has been actively engaged to act as justice enforcers in criminal offenses in the field of Information and Electronic Transactions, although not yet optimal